Jornalismo automatizado: inteligência artificial e robôs nas redações das organizações jornalísticas - Cabral, Laura Rayssa de Andrade (2022)
Based on Artificial Intelligence (AI) and through the rise of digital data, automation initiatives in journalism began to intensify in several countries around the world, causing implications that echo in journalists, journalistic organizations and different audiences. In Brazil, initiatives that make use of robots with AI are gaining strength, a reality similar to that of many countries, such as the United States, where automated journalism is expanding. Therefore, this dissertation aims to understand the dimensions of automated journalism, through the study of the functioning of robots with AI, and its implications in the newsrooms of journalistic organizations, in order to apprehend at what stage is automated journalism in Brazil. As an empirical methodology, we carried out a mapping of Brazilian journalistic initiatives that make use of robots with AI and a case study of two specific initiatives, the robots Fátima and Elas no Congresso. The main results obtained with the research point to the strengthening of automated journalism in Brazil, as an innovative practice in newsrooms; the constitution of new journalistic ecosystems in which human and non-human actors work together; the appreciation of human characteristics by journalists and the growing use of technologies with Artificial Intelligence in the present and future of journalism.